Elaboración de un plan de mejora del protocolo de mantenimiento de los equipos de perforación para la compañía Equion Energía Limited (2018)
For the solution of the problem proposed in the work of degree the first step was to know the current situation of the drilling equipment that the company Equion Energy LIMITED uses in its operation located in the region of Casanare (Colombia). Taking into account the information provided by Equion of the equipment with the highest failure frequency, a list of the equipment was made, its current condition and criteria of criticality were applied. Subsequently, the most critical teams were emphasized and an operational context of each team was elaborated. After this, it was proceeded to analyze the times that each equipment failed which were supplied by the Equion database, after this the mode and effect of faults of the respective equipment (AMEF) was made. Once the modes and effects of the failures of the studied equipment were determined, it was possible to establish the improvement activities for the maintenance protocol that is carried out in the drilling hole type AC currently operated.